2015
DOI: 10.1021/acs.molpharmaceut.5b00629
|View full text |Cite
|
Sign up to set email alerts
|

New Solid Forms of the Antiviral Drug Arbidol: Crystal Structures, Thermodynamic Stability, and Solubility

Abstract: Salts of the antiviral drug Arbidol (umifenovir) with pharmaceutically relevant benzoate and salicylate anions were obtained, and their crystal structures were described. For Arbidol salicylate, an unstable solvate with acetonitrile was also found and characterized. Analysis of the conformational preferences of the Arbidol molecule in the crystal structures showed that it adopts two types of conformations, namely "open" and "closed", both of which correspond to local conformational energy minima of the isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…However, no pharmacokinetic nor metabolite studies were performed from this mode of administration. In addition, salt engineering techniques were also used to prepare the methanesulfonic salt [ 12 ] and salicylate anions form [ 13 ] of ADL in order to improve the aqueous solubility and bioavailability. The methanesulfonic salt of arbidol exhibited a relatively higher peak plasma concentration (Cmax) and an increased area under curve (AUC0-t) compared with a commercial product indicating the improved bioavailability of the drug; however, it was not statistically justified.…”
Section: Introductionmentioning
confidence: 99%
“…However, no pharmacokinetic nor metabolite studies were performed from this mode of administration. In addition, salt engineering techniques were also used to prepare the methanesulfonic salt [ 12 ] and salicylate anions form [ 13 ] of ADL in order to improve the aqueous solubility and bioavailability. The methanesulfonic salt of arbidol exhibited a relatively higher peak plasma concentration (Cmax) and an increased area under curve (AUC0-t) compared with a commercial product indicating the improved bioavailability of the drug; however, it was not statistically justified.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, such information is obtained by co-crystal equilibrium solubility experiments conducted at different temperatures. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, there are works where two independent techniquessolubility calorimetry (to analyze the enthalpic term) and solubility measured by the saturation method (to analyze the Gibbs energy)are used to determine all the thermodynamic parameters. For example, Oliveira et al 32 studied the thermodynamics of [Carbamazepine + Saccharin] co-crystal formation by this method.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that in arbidol salts, there are two most common types of hydrogen bonds, forming ) 10 ( 2 2 R graph set supramolecular synthons [21]. In our previous work, salts of the antiviral drug arbidol with pharmaceutically relevant benzoate and salicylate anions have been obtained [23]. The ) 10 ( 2 2 R graph set supramolecular synthon was observed in both salts.…”
Section: Introductionmentioning
confidence: 92%